Developing the Australian mid-infrared spectroscopic database using data from the Australian Soil Resource Information System - Hicks, W.; Viscarra Rossel, Raphael; Tuomi, S. (2015)
We developed and tested spectroscopic models derived by partial least squares regression (PLSR) using data from the Commonwealth Scientific and Industrial Research Organisation's (CSIRO) national soil database (NatSoil) and soil samples from the Australian National Soil Archive. Models were constructed for 21 soil attributes, and their predictability assessed using the R2, ranged from 0.57 for bicarbonate extractable available phosphorus to 0.92 for the sum of the exchangeable bases. Investigating the spectral library coverage with a suite of 1484 unknown samples from a geochemical survey of Australian catchments, we found that the models could be used to predict many soil attributes in a geographically diverse set of samples.